Point-of-Care Ultrasound in Neurology – Report of the EAN SPN/ESNCH/ERcNsono Neuro-POCUS Working Group - Valaikiene, Jurgita; Schlachetzki, Felix; Azevedo, Elsa; Kaps, Manfred; Lochner, Piergiorgio; Katsanos, Aristeidis H.; Walter, Uwe; Baracchini, Claudio; Bartels, Eva; Školoudík, David (Ultraschall in der Medizin - European Journal of Ultrasound, 2022)
In the last decade, ultrasound examination in neurology has been undergoing a significant expansion of its modalities. In parallel, there is an increasing demand for rapid and high-quality diagnostics in various acute diseases in the prehospital setting, the emergency room, intensive care unit, and during surgical or interventional procedures. Due to the growing need for rapid answers to clinical questions, there is particular demand for diagnostic ultrasound imaging. The Neuro-POCUS working group, a joint project by the European Academy of Neurology Scientific Panel Neurosonology, the European Society of Neurosonology and Cerebral Hemodynamics, and the European Reference Centers in Neurosonology (EAN SPN/ESNCH/ERcNsono Neuro-POCUS working group), was given the task of creating a concept for point-of-care ultrasound in neurology called “Neuro-POCUS”. We introduce here a new ultrasound examination concept called point-of-care ultrasound in neurology (Neuro-POCUS) designed to streamline conclusive imaging outside of the ultrasound center, directly at the bedside. The aim of this study is to encourage neurologists to add quick and disease-oriented Neuro-POCUS to accompany the patient in the critical phase as an adjunct not a substitution for computed tomography, magnetic resonance imaging, or standard comprehensive neurosonology examination. Another goal is to avoid unwanted complications during imaging-free periods, ultimately resulting in advantages for the patient.
Keywords: neurology; neurocritical care; stroke; point-of-care ultrasound; ultrasound